Intensive cycling of nickel in a New Caledonian forest dominated by hyperaccumulator trees. (6th August 2021) - Paul, Adrian L. D.; Isnard, Sandrine; Wawryk, Christine M.; Erskine, Peter D.; Echevarria, Guillaume; Baker, Alan J. M.; Kirby, Jason K.; van der Ent, Antony
SUMMARY: The hyperaccumulator Pycnandra acuminata is a New Caledonian rainforest tree known to have the highest concentration of nickel in any living organism, with 25 wt% nickel in its latex. All trees (with a diameter of >10 cm) and soil profiles in a 0.25‐hectare permanent plot were sampled to assess the biogeochemical compartmentalisation of nickel in a dense stand of P. acuminata trees. Nickel stable isotope analysis permitted insights into the cycling of nickel in this ecosystem. The total tree biomass of the plot was calculated to be 281 tonnes ha −1, which contained 0.44 kg of cobalt, 49.1 kg of manganese, 257 kg of nickel and 6.76 kg of zinc. Nickel stable isotope analysis identified the biotic origin of the nickel in the soil upper layers, with P. acuminata shoots enriched in lighter nickel isotopes. The δ 60 Ni latex signature suggests that long‐distance transport, radial xylem and phloem loading are at play in P. acuminata . Significance Statement: This study aimed to determine the extent to which large Ni hyperaccumulator trees affect the biochemical cycling of Ni and other trace elements in a rainforest ecosystem dominated by Pycnandra acuminata in New Caledonia. The use of nickel stable isotope analysis permitted insights into the cycling of nickel in this system and confirmed the biotic origins of the Ni present in the upper layers of the soil.